P280 USE OF SYSTEMIC THROMBOLYSIS IN HEMODYNAMICALLY UNSTABLE PULMONARY EMBOLISM PATIENTS WITH AND WITHOUT CARDIAC ARREST: DATA FROM THE IPER REGISTRY. (18th May 2022) - Zuin, M; Bilato, C; Bongarzoni, A; Zonzin, P; Casazza, F; Roncon, L
Abstract: Background: Systemic thrombolysis (ST) remains the treatment of choice in haemodynamically unstable patients with acute pulmonary embolism (PE). However, it remains frequently underused in clinical practice. The purpose of the study is to evaluate the use of ST in hemodynamically unstable PE patients with aand without acute cardiac arrest using the IPER registry. Materials and Methods: IPER is a multicentre, national, prospective, web–based registry based on 47 Italian hospitals. In this study, the population was divided into two groups: patients with (ACC) and without (No ACC) cardio–circulatory arrest at admission. Results: Of 1716 patients enrolled between September 2006 and August 2010, 201 (11.7%) [mean age 74 ± 14 years 127 females] were defined as high risk (i.e. haemodynamically unstable). Of these 59 (29.4%, mean age 76.4 ± 13.3 years, 40 females) were admitted with ACC while the remaining 142 (70.6, mean age 73.5 ± 13.7 years, 87 females) without. No differences were observed for venous thromboembolism risk factors, such as immobilization for more than three days, trauma, surgery within the previous 4 weeks, previous venous thromboembolism, history of heart failure, cancer and ischemic heart disease, among the two gropus. Mortality from all causes (62.7% vs 19.0, p < 0.001) and for acute PE (55.9% vs 9.9%, p < 0.001) was higher in ACC patients. Thrombolysis was administered in 82 (40.7%) of haemodynamically unstable patients and more frequently in ACC subjects (55.9% VSA 34.5%, p = 0.005) (Figure 1, panel A). The administration of systemic thrombolysis increased with aging in the No ACC group but showed a significant reduction in over–octogenarian patients (Figure 1, panel B). Major bleeding complications following reperfusive treatment were observed in 8 patients (3.9%); among these, intracranial hemorrhage was registered in 2.4% of cases. Conclusions: Although systemic thrombolysis remains the first–line treatment in patients with hemodynamically unstable acute PE and is capable of improving both the mortality and morbidity, it continues to be underused in daily clinical practice, often for fear of major bleeding complications.